Effective curriculum for teaching L2 writing principles and techniques - Hinkel, Eli (ESL & applied linguistics professional series, 2015)
Effective Curriculum for Teaching L2 Writing sets out a clear big picture for curricular thinking about L2 writing pedagogy and offers a step-by-step guide to curriculum design with practical examples and illustrations. Its main purpose is to help pre-service and practicing teachers design courses for teaching academic writing and to do this as efficiently and effectively as possible. Bringing together the what and the how-to with research-based principles, what sets this book apart is its overarching focus on language pedagogy and language building.